MOLECULAR-GENETIC AND SERUM DISORDERS MARKERS OF FOLATE METABOLISM IN PATIENTS PROLIFERATIVE DISEASE AND BREAST CANCER - A. V. Markovsky; N. N. Strambovskaya; P. P. Tereshkov (Сибирский онкологический журнал)
Aim: to study the relationship between homocysteine, cysteine and glutathione in blood serum and various single nucleotide polymorphisms (SNPs) of genes involved in folate metabolism in patients with proliferative breast disease and breast cancer. Material and methods. The study included 112 patients with proliferative breast lesions and breast cancer in Transbaikalia. The control group consisted of 144 women having no breast cancer. Blood levels of homocysteine, cysteine and glutathione were evaluated by HPLC (high performance liquid chromatography). Genotyping was performed by polymerase chain reaction with the detection of amplification product in real-time. Results. Molecular-genetic testing revealed no association between breast disease and genetic polymorphisms of MTHFR(C677T), MTHFR(A1298C), MTR(A2756G), MTRR(A66G) in women with proliferative breast lesions and breast cancer, however, in contrast to the control group, the concentrations of homocysteine and glutathione were increased.